Cheerleaders, jocks, nerds and "the man": popular representations of schooling in modern television - Solem, Allison, author; O'Donnell-Allen, Cindy, advisor; Sloane, Sarah, committee member; Mao, KuoRay, committee member (Colorado State University. Libraries, 2018)
In recent years, the availability of media has increased and adolescents are engaged with some type of media for most of the day. However, television remains one of the most popular mediums in America, despite increases in time spent on other forms of electronic media. Scholars have studied movies and their potential as "equipment for living," a central theme in Burke's Philosophy of Literary Form that asserts that fictional works inform our values, experiences, and expectations. This study aims to prove that television is also equipment for living for adolescents, and that they learn school-specific lessons from programs depicting a schooling environment. By analyzing three popular and current television programs and looking for school-specific character archetypes within those narratives, this study aims to determine what lessons secondary students learn about the purpose of school and the schooling experience. The results show that current television programs reflect broad cultural views about education and include fears about bullying and school shootings, as well as assumptions that secondary schools do not meet the needs of all of their students. The study also revealed cultural perceptions on school staff as uninterested in serving student needs. However, some programs challenge stereotypes and present more realistic representations of students, teachers, and administration in secondary schools.